St. Kitts and Nevis : 2006 Article IV Consultation-Staff Report; Staff Statement; and Public Information Notice on the Executive Board Discussion. (IMF Staff Country Reports; Country Report, 2007)
This 2006 Article IV Consultation highlights that despite the closure of the sugar industry, economic growth in St. Kitts and Nevis has accelerated. In 2006, the economy is estimated to have recorded its third consecutive year of strong growth, projected at 4 1\2 percent in 2006, with good prospects for 2007. Although the current account deficit remains large, it has been mainly financed by foreign direct investment, and competitiveness appears to be improving. Fiscal imbalances have improved significantly, reflecting both policy adjustments and continued growth.